亚院第四学期学生使用汉语形容词 “热情”与“热心”的能力考察 KEMAMPUAN PENGGUNAAN KATA SIFAT “REQING” DAN “REXIN” PADA MAHASISWA STBA-PIA SEMESTER IV T.A 2020/2021 - Sinar Anwar; Agnesya Liangga (Journal of Language, Literature and Teaching, 2022)
The purpose of this study was to describe the ability of Semester IV STBA-PIA Medan students in using the adjective rexin and reqing. To achieve this goal, the researcher used a quantitative descriptive research design where the population was 113 students, and the sample was taken using the Simple Random Sampling technique to 23 students in the Fourth semester of STBA-PIA Medan T.A. 2020/2021 as the sample of this research. The instrument and data collection technique used is to give test questions to the sample. The validity of this study uses content validity, and the calculation of the test questions for each word is 10 questions using the KR-20 Formula. The reliability value of the reqing adjective test instrument is high, it is 0.612 and the reliability value of the rexin adjective test instrument is also high, it is 0.638. Analysis of students' ability test results in using reqing adjectives shows that from the range of values the highest score obtained is 100 and the lowest score is 50, the mode and median values are 70, the standard deviation value is 15 and the average value is 71.74 which is included in the sufficient competent category. While the results of the student's ability to use the adjective rexin show that from the range of values the highest score obtained is 100 and the lowest score is 40, the mode and median values are 70, the standard deviation value is 14 and the average score is 72.61 which is included in the in the fairly competent category.Key Words: Usability, Adjective, Rexin, Reqing